Using Blockchain Technology as an Accounting Information System - شيرين العلاوى (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ)
The purpose of the study is to determine the possibility of using blockchain technology as an Accounting Information System (AIS). The study exhibits the theoretical background of blockchain technology. As well as different characteristics of blockchain technology and its possibility to be used as accounting information system. The study depended on a field study to test the study Hypotheses. The results indicated that there is no definite approach regarding using blockchain as AIS. Up to now, researchers have different opinion, some argued that using blockchain based AIS would bring a huge benefit to the accounting industry and it should be merged with ERP systems. While others argued that there are already current systems that provide what blockchain expected to provide, so there is no need to consider it. On the other hand, others consider using Blockchain as a System (BaaS) since it would be very hard to merge in current systems.